Human herpesvirus 6 and epilepsy. Issue 4 (8th August 2021) - Theodore, William H.; Leibovitch, Emily; Billioux, Bridgette J.; Inati, Sara K.; Zaghloul, Kareem; Heiss, John; Gaillard, William D.; Jacobson, Steven
Abstract: We investigated the association between human herpesvirus 6 (HHV‐6) and mesial temporal sclerosis (MTS) in 87 patients who had surgery for drug‐resistant epilepsy. Fifty‐four had MTS, 22 focal cortical dysplasia (FCD), four tumors, three vascular malformations, and three a history of encephalitis. We extracted DNA from fresh brain tissue immediately after surgery and performed viral detection with quantitative real‐time polymerase chain reaction (PCR) or digital droplet PCR specific for HHV‐6A and HHV‐6B. Tissue was studied with standard clinical techniques, including hematoxylin and eosin, glial fibrillary acidic protein, and NeuN stains. Twenty‐nine of 54 patients with MTS, six of 23 with focal cortical dysplasia (FCD), and one of three with a history of encephalitis were positive for HHV‐6 ( P  < .02). Febrile seizure history was not associated with HHV‐6 detection. Patients with MTS had significantly lower seizure onset age than those with other pathologies. Thirteen patients had positron emission tomography with [11C]PBR28, a marker for reactive astrocytes and activated microglia; there was a trend for HHV‐6‐positive patients to have higher binding in their seizure foci, suggesting inflammation. Our study supports a potential role for HHV‐6 in the etiology of MTS.